Rudolf Hilferding the tragedy of a German Social Democrat - Smaldone, William 1958- (Northern Illinois Univ. Press, 1998)
"Until his death in a Gestapo prison cell, Rudolf Hilferding was one of Europe's most prominent socialist theorists and politicians. A leading economic thinker in the European socialist movement and an important politician in the German Social Democratic Party, he served as Weimar finance minister at the height of the inflation of 1923 and again at the onset of the depression in 1928. At a time when Germany faced one economic and political crisis after another, he led Social Democracy's efforts to strengthen the republic and to achieve its socialist objectives." "This biography illustrates how Hilferding's personal and intellectual journey reflected the failures of social democracy in its confrontation with nazism and communism." "This study will be of interest to scholars and students of modern German and European history, the history of socialism, political theory, and economic thought."--BOOK JACKET.